Tax Treaty Abuse: Is Canada responding effectively? - Loomer, Geoffrey T. (Working Papers, 2009)
This paper explores the means by which tax authorities worldwide seek to strengthen their tax treaties, through safeguards of varying nature and scope, in order to identify and prevent what they consider to be abuse of such treaties. These means of challenge may be grouped under two headings: purposive approaches to treaty interpretation, particularly with respect to the terms 'person', 'resident' and 'beneficial ownership'; and broader responses to unacceptable tax avoidance, specifically reliance on treaty anti-abuse principles and domestic anti-avoidance rules. The Canadian response is evinced by two recent cases in which the government unsuccessfully challenged 'treaty shopping' arrangements, MIL (Investments) SA v Canada and Prevost Car Inc v Canada. Building on the existing literature regarding tax treaty shopping and other forms of tax treaty abuse, this work seeks not only to describe and explain the responses to treaty abuse but to make a critical inquiry into the essence of such abuse, particularly as it appears to be viewed by the Canadian revenue authorities. It is argued that the Canadian response to tax treaty abuse is inadequate, largely because it conflates multiple approaches and fails to address a key concern: the existence or lack of genuine economic establishment in the treaty state. The paper concludes with some suggestions for fashioning a more coherent and intellectually honest response to tax treaty abuse.